«Fratres, omni die videtis cum vadit istud regnum in perdicionem»: Abbo of Saint-Germain and the Crisis of 888 - West, Charles (Reti Medievali Rivista, 2016)
Historians often consider the year 888 to have marked the effective end of the Carolingian empire established by Charlemagne. This paper explores the issue from the perspective of a contemporary author, the monk Abbo of Saint-Germain des Prés. Abbo is today best known for his poem about the Viking sieges of Paris, but he later also compiled a fascinating and rather overlooked set of sermons. Taken together, these texts offer an insight into contemporary responses to the “crisis” that followed the deposition and death of Emperor Charles the Fat.